Existence of Islamic Education in the Contemporary Era Perspective Post Colonial - Nurhalim (Journal of Educational Administration, 2022)
The existence of post-colonial Contemporary Islamic education cannot be separated from its historical dynamics in the colonial era, Islamic education was "forced" to face the challenges of secular education as part of the propaganda of the European colonialists, giving rise to various reactions from opposing attitudes as the attitudes of traditionalists, neo-traditionalists, reformers, and modernists. . The dualism of the post-colonial Islamic education system is one of the significant effects of the colonial heritage which is very difficult to resolve, this is due to the colonial government's discriminatory treatment of Islamic education so that Islamic education seeks and determines its own form as an educational institution that is separate from the education system managed by the State. The challenges and problems of Islamic education are increasingly complex in the face of global transformation, and advances in science and technology. The rapid flow of modernization is increasingly unstoppable with various positive and negative effects on human life. The contemporary era does not only occur at the global level, but the modern era is also part of the life of Muslim society. The importance of Islamic identity surviving the onslaught of secularization and globalization is an integral part of the task of Islamic education, so the transformation of the Islamic education system becomes a necessity to answer and become a solution for the community. The method used is a literature study with a qualitative research type through an analytical approach to literature review. Previous research as a source of information on the development of Islamic Religious Education research studies. The presence of an Integrated Islamic School in Indonesia is part of the reconstruction and modernization of the Islamic education system by integrating and integrating elements of management and curriculum content, learning methods, and community involvement in school governance so that its presence becomes part of an alternative solution as an Islamic educational institution in the era of contemporary, but the presence of the Integrated Islamic School as an upper secondary educational institution with high-cost standards so that it is not yet accessible to the average Muslim community